THE β-AMYLASE GENES OF GRASSES AND A PHYLOGENETIC ANALYSIS OF THE GREEN PLANTS - Stratula , O.R.; Kotseruba , V.V.; Kalendar , R.N. (Eurasian Journal of Applied Biotechnology, 2014)
A new molecular marker – nuclear gene BAMY, encoding β-amylase enzyme which carries out hydrolysis mainly 1,4-α-glucan maltohydrase in amylose, amylopectin, glycogen, and other maltooligosaccharides for example monocotyledonous and dicotyledonous plant species has been studied. We cloned and sequenced the nucleotide sequences of the genes of BAMY for cereal species and obtained their corresponding amino acid sequences. Based on the data on DNA sequences BAMY, as well as the amino acid sequences of β-amylase showing phylogenetic relationships between genera, families, orders and classes of plants. The result of phylogenetic analysis corresponds to the modern concept of the taxonomy of the analysed species. The studied gene BAMY promising for further exploration and use as a marker for molecular identification in the analysis of near and distant species of the plant kingdom. We obtained the genera and species-specific EPIC-exons primers sets to amplify BAMY gene fragments representatives of the family Poaceae, which enable them to use the taxonomic analysis of a wide range. The PCR primers sets allowed to use for screening a collection of species of grasses and established their inter- and intraspecific variability. This approach allows us to predict accessory an unknown genomic DNA sequences to known species, genera, families or classes of plants.